Final Demand Equations in W8D-2010 Model - Gosińska, Emilia; Leszkiewicz-Kędzior, Katarzyna; Welfe, Władysław (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This paper presents the specification of equations explaining the main components of final demand, i.e. the consumption demand of households, the consumption demand of public institutions, the demand for investment goods, the demand for inventories and reserves, the export and the import. To model the household's consumption two approaches have been used: the traditional one where the main role is attributed to the current disposable income of households and the other in which expectations are crucial to economic decision making, following the life cycle hypothesis. The demand for investment goods by firms is shaped allowing for an accelerator and the rate of capacity utilization. The user costs constrain the demand, there is also a substitution effect. What is more, an attempt was undertaken to introduce as an additional explanatory variable proxy for the risk premium. The best results obtained for the risk expressed as the ratio of budget deficit to the GDP. Exports and imports equations are built in a traditional manner allowing for the level of respective activities and relative prices.